Prolegomena to Agapeology: Reflections on Love as Panexperiential Phenomenon - Lenart Škof (Religions)
This paper is an attempt to reflect upon the hidden or mysterious logic of love as an ontological and panexperiential phenomenon. In our attempt, we are crossing the fields of philosophy, spirituality, and contemporary research in psi phenomena (also known as paranormal phenomena) and investigating some historical conditions of margins and disputes between the disciplines based on David Ray Griffin’s work, Parapsychology, Philosophy, and Spirituality. In the main part of this paper, we present the aesthetic theory of force by Christoph Menke and follow his rich analyses on the hidden, obscure layers of the soul. Based on these analyses, we present our own thesis on agapeology as being related both to psi phenomena and aesthetic phenomena. Throughout the history of religion and Western science, magical and miraculous events were too often relegated to the domain of faith or superstition and dismissed almost entirely. In the final parts of this paper, we aim to show that using the approaches of synchronicity (C.G. Jung) and ontology of the ground (F.W.J., Schelling) and acknowledging the phenomena known as quantum entanglement (C. Keller), we can postulate an underlying nexus, providing us with an access to the agapeistic effects of what we idiosyncratically call the phenomenon of dark love.